Impact of Tin Fluoride Additive on the Properties of Mixed Tin‐Lead Iodide Perovskite Semiconductors. (20th September 2020) - Savill, Kimberley J.; Ulatowski, Aleksander M.; Farrar, Michael D.; Johnston, Michael B.; Snaith, Henry J.; Herz, Laura M.
Abstract: Mixed tin‐lead halide perovskites are promising low‐bandgap absorbers for all‐perovskite tandem solar cells that offer higher efficiencies than single‐junction devices. A significant barrier to higher performance and stability is the ready oxidation of tin, commonly mitigated by various additives whose impact is still poorly understood for mixed tin‐lead perovskites. Here, the effects of the commonly used SnF2 additive are revealed for FA0 . 83 Cs0 . 17 Sn x Pb1− x I3 perovskites across the full compositional lead‐tin range and SnF2 percentages of 0.1–20% of precursor tin content. SnF2 addition causes a significant reduction in the background hole density associated with tin vacancies, yielding longer photoluminescence lifetimes, decreased energetic disorder, reduced Burstein–Moss shifts, and higher charge‐carrier mobilities. Such effects are optimized for SnF2 addition of 1%, while for 5% SnF2 and above, additional nonradiative recombination pathways begin to appear. It is further found that the addition of SnF2 reduces a tetragonal distortion in the perovskite structure deriving from the presence of tin vacancies that cause strain, particularly for high tin content. The optical phonon response associated with inorganic lattice vibrations is further explored, exhibiting a shift to higher frequency and significant broadening with increasing tin fraction, in accordance with lower effective atomic metal masses and shorter phonon lifetimes. Abstract : The impact of SnF2 on FA0 . 83 Cs0 . 17 Sn x Pb1− x I3 perovskite thin films is examined for additive amounts varying between 0.1% and 20%. Structural distortion from lattice strain is reduced by SnF2 addition. Lower background hole doping, longer photoluminescence lifetimes, and higher charge‐carrier mobilities are observed with as little as 1% SnF2 added. Larger quantities of the additive introduce defects alongside these beneficial effects.